Tularemia in Germany—A Re-emerging Zoonosis - Faber, Mirko; Heuner, Klaus; Jacob, Daniela; Grunow, Roland (Frontiers in Cellular and Infection Microbiology, 2018)
Tularemia, also known as “rabbit fever,” is a zoonosis caused by the facultative intracellular, gram-negative bacterium Francisella tularensis. Infection occurs through contact with infected animals (often hares), arthropod vectors (such as ticks or deer flies), inhalation of contaminated dust or through contaminated food and water. In this review, we would like to provide an overview of the current epidemiological situation in Germany using published studies and case reports, an analysis of recent surveillance data and our own experience from the laboratory diagnostics, and investigation of cases. While in Germany tularemia is a rarely reported disease, there is evidence of recent re-emergence. We also describe some peculiarities that were observed in Germany, such as a broad genetic diversity, and a recently discovered new genus of Francisella and protracted or severe clinical courses of infections with the subspecies holarctica. Because tularemia is a zoonosis, we also touch upon the situation in the animal reservoir and one-health aspects of this disease. Apparently, many pieces of the puzzle need to be found and put into place before the complex interaction between wildlife, the environment and humans are fully understood. Funding for investigations into rare diseases is scarce. Therefore, combining efforts in several countries in the framework of international projects may be necessary to advance further our understanding of this serious but also scientifically interesting disease.